High Serum Alkaline Phosphatase Flare after First-Line Androgen Deprivation Therapy Predicts Poor Prognosis in Metastatic Prostate Cancer Patients Treated with Second-Generation Androgen Receptor Targeted Therapy - Satoko Kojima; Hiroshi Masuda; Takahito Suyama; Kyokushin Hou; Kousuke Mikami; Kazuhiro Araki; Yukio Naya (Prostate Cancer)
Objectives. To determine whether an alkaline phosphatase (ALP) flare after androgen deprivation therapy (ADT) is associated with the treatment response in castration-resistant prostate cancer (CRPC) and predicts the prognosis of metastatic prostate cancer (PCa) patients. Methods. One hundred and nineteen patients diagnosed with metastatic PCa between 2008 and 2017 were retrospectively studied. The ALP flare ratio was calculated as the ratio of ALP levels 1 month after beginning ADT to ALP levels at diagnosis. The association of the ALP flare ratio with the prostate-specific antigen (PSA) response to CRPC treatment (second-generation androgen receptor targeted therapy (ART) or docetaxel), time to CRPC, and overall survival (OS) were investigated. Results. The time to CRPC and OS was significantly longer in patients with an ALP flare ratio less than 1.33 compared to a ratio more than 1.33. No difference in PSA response was seen regarding the ALP flare ratio in both ART and docetaxel treatment. Second-generation ART-treated patients with a low ALP flare ratio showed longer OS than those with a higher ALP flare ratio (p=0.0367). However, no difference was seen between a high and low ALP flare ratio (p=0.8054) in docetaxel-treated patients. The ALP flare ratio was the most significant prognostic factor for OS (p<0.0001). Conclusions. A higher ALP flare ratio after first-line ADT was a significant prognostic factor in metastatic PCa, especially in patients treated with second-generation ART for CRPC. Chemotherapy for patients with a higher ALP flare ratio 1 month after induction of ADT may be a clinically relevant decision.